Preventing Foodborne Illness: Listeriosis - Keith R. Schneider; Renée M. Goodrich-Schneider; Michael A. Hubbard; Susanna Richardson (EDIS)
Listeriosis is one of several foodborne diseases that are often reported in the scientific and popular press. In the United States, it affects about 1,600 people every year, with about 270 of those cases resulting in death. It expresses itself in the affected person by means of septicemia, meningitis, and/or encephalitis. Pregnant women who have intrauterine or cervical infections caused by L. monocytogenes in their second or third trimesters may spontaneously abort the fetus or produce a stillbirth. Influenza-type symptoms, which may include continuous fever, usually precede the aforementioned disorders. This 4-page fact sheet was written by Keith R. Schneider, Renée Goodrich-Schneider, Michael A. Hubbard, and Susanna Richardson, and published by the UF Department of Food Science and Human Nutrition, March 2013.